The Role of Religious Value Co-Creation and Employee Customer Identification on Trust and Purchase Intention in Gold Installment Products of PT Bank Syariah Indonesia TBK - Soerono, Mahendra Nusanto; Wikaningrum, Tri (UNISSULA, 2025)
This study aims to analyze the role of Religious Value Co-Creation and Employee Customer Identification on Trust and Purchase Intention in gold installment products at PT Bank Syariah Indonesia Tbk. The research gap that researchers have obtained shows inconsistent results, where some stated that religious value, co-creation, and employee customer identification affect purchase intention, and others stated that religious value, co-creation, and employee customer identification signified no effect on purchase intention. Interest in religious-based investment products, including Bank Syariah Indonesia's gold installment plans, can be influenced by religious value co-creation. In addition to religious value co-creation, employee-customer identification is another variable that can influence consumer interest. This study incorporates customer trust as a variable to bridge the gap. The sample was 110 Bank Syariah Indonesia customers using the hair formula with a purposive sampling technique. The process of data collection was conducted using a questionnaire. The results obtained within this study demonstrate that religious value co-creation displays a significantly positive effect on trust, employee customer identification shows a significantly positive effect on trust, religious value co-creation shows a significantly positive impact on purchase intention, employee customer identification shows a significantly positive impact on purchase intention, trust shows a significantly positive effect on purchase intention, trust mediates the positive and significant impact of religious value co-creation on purchase intention and trust mediates the positive and significant effect of employee customer identification on purchase intention.